2012
DOI: 10.1021/ol3026582
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanical Transition-State Analysis Reveals the Precise Origin of Stereoselectivity in Chiral Quaternary Cinchonidinium Phase-Transfer Catalyzed Enolate Allylation

Abstract: Density functional theory was used to model glycinate enolate binding and enantiomeric allylation transition states mediated by the cinchonidinium phase-transfer catalyst 2. Transition states show oxy-anion-ammonium interactions in contrast to π-face interactions in the ground states. The details of stereoselectivity are described within the quaternary ammonium-tetrahedron face model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…(2H, s), 6.76 (1H, s), 2.38 (3H, s). 13 C-NMR (68 MHz, CDCl3) δ: 139.9, 130.1, 128.5, 121.8 (q, J = 274.9…”
Section: 1'-(5-methyl-13-phenylene)bis(222-trifluoroethanone)mentioning
confidence: 99%
See 2 more Smart Citations
“…(2H, s), 6.76 (1H, s), 2.38 (3H, s). 13 C-NMR (68 MHz, CDCl3) δ: 139.9, 130.1, 128.5, 121.8 (q, J = 274.9…”
Section: 1'-(5-methyl-13-phenylene)bis(222-trifluoroethanone)mentioning
confidence: 99%
“…H-NMR (270 MHz, CDCl3) δ: 7.90 (4H, m,), 7.41-7.13 (7H, m), 2.52-2.41 (9H, m) 13. C-NMR (68 MHz, CDCl3) δ: 179.5 (q, J = 36.3 Hz), 140.8, 136.5, 136.5, 130.8, 128.7, 128.7, 128.7, 116.3 (q, J = 291.3 Hz), 21.3 (3C).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that the theoretical chemistry can offer alternative opportunity to study the mechanism, especially the untouchable transition states, besides experimental procedures. Recently, overcoming the large and flexible disadvantage of cinchona-derived PTC catalysts, some calculations were performed to throw new insights on PTC reactions. Lipkowitz and O’Donnell conducted a precedent theoretical study on the interaction between the N -benzylcinchoninium cation and Schiff base-derived enolates with molecular dynamics and semiempirical quantum theory in 1991 . They found the Z -enolates selective binding on the front side of the N -benzylcinchoninium may account for the observed enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…NOE correlations study of PTC 2 with borohydride ion 6 indicated the borohydride occupies the F1 face of PTC 2. Computational simulation 7 also described the stable transition states where an enolate locates on the F1 face.…”
mentioning
confidence: 99%